Two different factors bind to the alpha-domain of the polyoma virus enhancer, one of which also interacts with the SV40 and c-fos enhancers. - Piette, J (1987)
Two nuclear factors from mouse 3T6 cells bind to a 22-bp segment constituting the alpha-domain of the polyoma virus enhancer. Binding of each factor can be competed out selectively by the appropriate double-stranded oligonucleotide, indicating that this binding is not strictly cooperative. Sequence homology between the two binding sites and the similar size of the protected regions may indicate that both factors, PEA1 and PEA2, are closely related. The binding site of PEA1 is centered on a sequence showing strong homology to the SV40 enhancer, the binding site of PEA2 is located immediately adjacent to it and shows a strong homology to the c-fos enhancer. Surprisingly, both SV40 and c-fos enhancers interact with PEA1, probably due to the presence of an extra base pair relative to c-fos in the PEA2 site. Factor PEA1 is probably identical to the recently described activator protein 1 (AP1).